Perancaangan Sistem Informasi Manajemen Permintaan Barang Berbasis Web pada PT MNC SKY VISION Tbk - Agustian, Bobi; Kusyadi, Irpan; Jaelani, Yusep (Jurnal Informatika Universitas Pamulang, 2019)
At present, the world has entered the era of information-based competition. Information becomes a valuable asset for a business institution in winning business competition. At PT MNC Sky Vision Tbk is currently using an information system in the form of the use of computer equipment in carrying out its work activities, but in processing data on demand for goods currently in processing data is still less efficient, fast, accurate, and there are still errors in the monthly report, because when In the average daily demand for goods there are 10 requests, both departments / divisions and from branch offices namely KPP, KPD and KPU, which number around 46 departments / divisions and 75 branch offices, for the number of goods requested by the Demand Management Information System Web-Based Goods at PT. MNC Sky Vision Tbk. In one transaction, there were 8 types out of a total of 738 types of goods, so in the process of recapitulating data, demand for goods requires a long time either in adding data, changing data, deleting data and searching data for items needed in a month. Based on these problems, it is needed an application in processing demand data, especially office stationery (ATK) and other supporting operational activities of the office. In this study, the data collection method uses observation, interviews and literature studies. The application is compiled with the procedure of development stage which includes analysis of needs, making data flow diagrams, implementation using PHP as a programming language and MySql as the database. From the research conducted, a Web-based demand management information system software is produced, which can help in day-to-day office operations, namely data storage or data recap and also avoid losses due to human error.